5G technology enabling unmanned offshore platform - Rujun XIA (Dianxin kexue)
The exploration, development and production of offshore oil are characterized by “high risk, high investment and high technology”.Many restrictive factors, such as the inferiority of offshore natural environment, the high risk of oil and gas production, and the demand for communication signal stability, equipment operation reliability and timely emergency support, make it more difficult to realize unmanned offshore platform.Based on the analysis of the status quo, development trend and implementation requirements of unmanned offshore platform, a 5G communication scheme for unmanned offshore platform was proposed.5G network is built between the central platform and the wellhead platform, and the transmission rate, distance, delay and other field tests were carried out.The test results show that 5G communication meets the requirements of high reliability and low delay stable transmission, such as security monitoring, remote control, emergency stop and so on.The scheme has accumulated experience and laid a solid foundation for the construction of an unmanned offshore platform.